Teacher-learner Cooperation to Develop Research Skills in Lower Elementary School - Drelinga, Elga; Krastiņa, Elfrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
To preserve the planet as a habitat for future generations, humans need to act creatively and responsibly, and perceive themselves as a part of the Universe. It follows that nowadays education should be sustainability oriented. The learning process should be carefully shaped to enable learners to interact with their teacher and thereby construct personally significant knowledge and develop research skills. Project work is a form of learning which affords ample opportunities to acquire such vital knowledge and skills. This study aims to investigate how teachers supervise project work to support the development of research skills among lower elementary school learners. Teacher-learner cooperation is evaluated according to a set of criteria derived from appraising lower elementary school learners’ degree of independence. Data were collected by interviewing expert teachers (n=8) and observing one elementary school teachers’ (n=10) actions during their supervision of project work. An inductive approach to qualitative content analysis of these data focused on appraising positive experience and tracing the connection between the outcomes of the pedagogical process and lower elementary school learners’ level of research skills acquisition. The findings have important implications for further research.